168 Nursery diets formulated with deoxynivalenol-contaminated corn reduced growth performance but did not modulate the cutaneous hypersensitivity response to ovalbumin or candida albicans. (30th November 2020) - Lariviere, Elise Lafleur; Zhu, Cuilan; Zettell, Sabrina; Patterson, Rob; Huber, Lee-Anne
Abstract: A total of 144 newly weaned pigs (21 days of age) were used to determine the effect of deoxynivalenol (DON)-contaminated corn, with or without NutraMix™ supplementation, on growth performance and indices of immune system functionality during the nursery period. Pigs were randomly allocated to 24 pens of six pigs and assigned to 1 of 4 dietary treatments according to a 2X2 factorial design (n=6); treatments were fed for the 43±1-day nursery period in three phases (phases I, II, and III fed for 8, 14, and 21±1 days, respectively). The factors were clean or DON-contaminated corn and with (2 g/kg in complete diet) or without NutraMix™ supplementation. The DON diets were formulated to ensure a step-up in DON concentration for each phase (3, 4, and 5 ppm in phases I, II, and III, respectively; analyzed concentrations were 3, 3 and 4 ppm). Individual pig body weights and per pen feed intake were recorded weekly. Two pigs per pen were vaccinated against ovalbumin and candida albicans to measure humoral and cell-mediated immune responses by the cutaneous hypersensitivity response test. The ADG (600 vs 693±28 g) and ADFI (979 vs 1110±51 g) in phase III and final BW (25.2 vs 27.1±0.9 kg) were reduced for pigs fed contaminated corn (P< 0.005, P=0.088, and P< 0.05, respectively). NutraMix™ supplementation tended (P=0.086) to improve ADFI (181 vs 142±14 g) in the first week after weaning. All pigs responded to both ovalbumin and candida albicans during the cutaneous hypersensitivity response (P< 0.05), but DON nor NutraMix™ influenced the response. The DON-contaminated diets had the greatest impact on pig growth performance during phase III and when DON concentration was 4 ppm, with no modulation of the cutaneous hypersensitivity response. NutraMix™ supplementation during the early weaning period may be a means to stimulate nursery pig feed intake.